ANALYSIS OF GREEN ZONES AND HEAT ISLANDS OF ALMATY CITY BASED ON SATELLITE IMAGES (Journal of Geography and Environmental Management, 2022)
The ubiquitous process of urbanization leads to the expected trend of population growth that will live on the territory of urban space. The image of urban organization of life leads to an increase in anthropogenic impact on the environment and a decrease in the level of interaction with natural resources. Population growth, or rather an increase in population density within an urban area that does not correspond to quantitative indicators, leads to a change in climatic indicators, which will subsequently affect the quality of life of citizens. The purpose of this scientific study was to identify green areas indicating the coverage of the urban area based on the definition of heat islands and classification by land cover based on satellite images. The scientific significance of the study was justified by the trend aimed at improving urban spaces and improving the quality of life of urban residents. The research methodology consisted in processing satellite images for further reclassification according to generally accepted standards, taking into account the individual indicators of the city of Almaty. The main result of the study was the identification of the zones most unsuitable for the quality of life, and the conclusion was recommendations for improving the environmental situation based on surface temperature indicators that allow identifying heat islands associated with a low quality indicator of the standard of living within the city of Almaty. The value of the research was aimed at developing theoretical theses for subsequent implementation in potential projects to improve the quality of life of residents of Almaty.
Keywords: Green zones, heat islands, geoinformation system, surface temperature, radiation of the Earth's surface, geospatial data, statistical analysis, remote sensing, cartography, spatial analysis and data science, buffer zones, network analysis, vegetation cover.